Recent Applications of C1-Symmetric Bis(oxazoline)-Containing Ligands in Asymmetric Catalysis - O’Reilly, Steven; Guiry, Patrick J. (Synthesis, 2014)
Bis(oxazolines) are a well-known class of ligands in the area of asymmetric catalysis. Most of these ligands are C2-symmetric due to the synthetic route employed for their synthesis. This review article summarizes the recent progress of the closely related, but relatively unexplored, C1-symmetric bis(oxazoline) ligands and compares and contrasts the two where applicable.1 Introduction2 Bis(oxazolines)2.1 Bis(oxazolines) with Differentially Substituted Oxazolines2.2 Bis(oxazolines) with Asymmetrically Substituted Linking Unit2.3 Bis(oxazolines) with Differentially Substituted Oxazolines and Asymmetrically Substituted Linking Unit3 Conclusion
Keywords: oxazoline; C1-symmetric; ligands; asymmetric catalysis; transition metals